A Versatile Optical Clearing Protocol for Deep Tissue Imaging of Fluorescent Proteins in Arabidopsis thaliana - Musielak, Thomas J.; Slane, Daniel; Liebig, Christian; Bayer, Martin (PLOS ONE, 2016)
Confocal microscopy is widely used to visualize gene expression patterns and developmental processes in plants. However, the imaging of plant tissue can be challenging due to its opacity, which often makes previous immersion in a clearing agent necessary. Many commonly-used chemicals suffer either from their incompatibility with fluorescent proteins or their complex and lengthy application. 2,2'-thiodiethanol (TDE) has recently been described as a clearing agent with an emphasis on high resolution microscopy due to its potential to adjust the refractive index. Here, we evaluate the use of TDE-based clearing for confocal as well as two-photon microscopy in various Arabidopsis thaliana tissue types. We demonstrate that tissue fixation is a mandatory prerequisite for the use of TDE, in order to preserve tissue integrity and fluorescent protein activity. TDE concentrations between 50–70% are a good compromise for imaging of technically challenging tissue to achieve good clearing without affecting fluorescent protein activity. TDE-based clearing is simple and rapid to use and allows for a flexible experimental setup while facilitating high quality imaging.